Regional and product profile of the postindustrial service economy of Kazakhstan - Beisenova , Zh.Zh. (BUKETOV BUSINESS REVIEW, 2017)
The service sector of the Kazakhstan economy needs further reform and rapidly accelerating development. This sector is called to play a crucial role in the process of building a post-industrial society, as demonstrated by the world experience of creation of a modern functionally efficient market systems of postindustrial type. In the article the analysis of the share of different types of post-industrial services economy leads to the conclusion that the differences between regions appear significant. At the same time, confirms the trend of increasing uniformity in the distribution of production of services in the regions of Kazakhstan and at the same time growth trends for individual types of services in the economies of regions that corresponds to the growth of their share in the economy as a whole. For certain types of post-industrial services, we conducted a rating of the regions of Kazakhstan and identify the areas that are the leaders for each individual service on the basis of the analysis of the structure of the services provided for each of the varieties. On the basis of rating the structure of the volume of services rendered was determined by the regional profiles of regions and the regions grouped according to profile types based on the method of absolute differences. A method of absolute differences allows us to identify groups within which the difference in the value of the considered indicator is less than between groups. Jump in the values allow one or another degree of certainty to allocate the group.